Asymmetric Organocatalytic 1, 4‐Addition Reactions Starting from Enals with gem‐Difluoroalkyl Side Chains. Issue 4 (19th December 2012) - Khalaf, Ali; Grée, Danielle; Abdallah, Hassan; Jaber, Nada; Hachem, Ali; Grée, René
Abstract: gem ‐Difluoroenals are excellent substrates for asymmetric organocatalytic 1, 4‐additions of thiols and anilines. By using diarylsilylprolinol ether as a catalyst, good to excellent yields with ee values in the same range (up to 98 %) were obtained. The CF2 R group strongly activates the enals towards these organocatalytic additions. Abstract : New chiral β‐thio and β‐amino aldehydes with CF2 R chains can be obtained in high yields with high ee values by asymmetric organocatalytic processes after selection of the appropriate catalyst and optimization of the reaction conditions.